Variability in Carcinus maenas Fecundity Along lagoons and estuaries of the Portuguese coast - N. Monteiro, J. (2022)
Although Carcinus maenas as a species is widely studied, research focusing on fecundity is still scarce. The main objective of this study was to evaluate size-fecundity relationships across diferent lagoons and estuaries, along the Portuguese coast, to understand how the local environment afects reproductive patterns. Between 2019 and 2020, ovigerous females were collected from the Southern (Ria Formosa and Ria de Alvor), Central (Rio Sado) and Northern regions (Ria de Aveiro) of Portugal, and the fecundity of each female was estimated by counting and weighing eggs. Morphometric relationships (carapace width–egg counting; egg counting–egg weight; body wet weight–egg weight; carapace width–body wet weight) were inferred from 180 egg-bearing females with a carapace width between 26.96 and 61.25 mm. A positive correlation between fecundity and the morphological parameters was observed. Diferences in fecundity were found among all systems, from northern to southern Portugal, varying between 22121 and 408538 eggs per female. Furthermore, a regional gradient was observed across regions, with lower temperature estuaries (Ria de Aveiro) displaying an increase in fecundity. The fecundity in Rio Sado was also afected by salinity. Fecundity diferences across regions were associated with hydrodynamics, temperature, and salinity diferences among systems. No statistically signifcant diferences were observed between Carapace Width—Body Wet Weight regressions performed in each studied system, indicating that, contrary to fecundity, the somatic growth of C. maenas is not afected by latitudinal or environmental conditions.